THE ROLE OF RADIOTHERAPY IN UTERINE CERVICAL CANCER - Henry Kodrat (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Uterine cervical cancer is the most common cancer in Indonesia. The purpose of the review is to describe diagnosis and staging, the basic principles of radiotherapy, the role of radiotherapy in cervical cancer treatment, and radiotherapy side effects. The goal of radiotherapy in cervical cancer consists of definitive, adjuvant, and palliative. Effort to increase radiation response also develops by administered small dose of chemotherapy as a radiosensitizer.Keywords: cancer, cervix, radiotherapy